Applications of blockchain technology - Mewada, Arvind; Singh, Nagendra; Ansari, Mohd. Aquib; Singh Yadav, Amrendra (Chapman & Hall/CRC, 2025)
This book explores the transformative potential of blockchain technology and shows how blockchain can promote equitable access to resources and bridge societal gaps. It examines blockchain's role in enhancing transparency, security, and decentralisation across various sectors and in society.
Keywords: Blockchains (Databases) -- Industrial applications.; elektronické knihy; electronic books